Reference and Limit Governors for Limit Protection of Turbofan Engines - Wenhao Xu; Muxuan Pan; Jiakun Qin; Jinquan Huang (Energies, 2019)
This paper proposes a novel architecture of limit protection including the references governors and limit governors and applies this architecture to limit protection in turbofan engines. References governors are designed as add-on schemes to a pre-stability engine control system that modifies reference commands to avoid constraints violation. Limit governors are proposed as an assistant part for references governors adjusting constraints to prevent references from stopping updates. The use of output admissible sets for a class of variable constraints is exploited to form invariant sets. Simulation results based on a turbofan engine model show that references governors with limit governors can effectively enforce the multiple constraints and provide enhanced engine thrust when steady violation occurs.